2020
DOI: 10.1038/s41598-020-78988-7
|View full text |Cite
|
Sign up to set email alerts
|

Altered diversity and composition of gut microbiota in Wilson's disease

Abstract: Wilson’s disease (WD) is an autosomal recessive inherited disorder of chronic copper toxicosis with high mortality and disability. Recent evidence suggests a correlation between dysbiosis in gut microbiome and multiple diseases such as genetic and metabolic disease. However, the impact of intestinal microbiota polymorphism in WD have not been fully elaborated and need to be explore for seeking some microbiota benefit for WD patients. In this study, the 16S rRNA sequencing was performed on fecal samples from 14… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Primary biliary cholangitis is associated with an elevated abundance of Streptococcus ( Lv et al, 2016 ; Tang et al, 2018 ; Furukawa et al, 2020 ), Veillonella ( Lv et al, 2016 ; Abe et al, 2018 ; Tang et al, 2018 ), Klebsiella ( Lv et al, 2016 ; Tang et al, 2018 ), Haemophilus ( Lv et al, 2016 ; Tang et al, 2018 ), and Lactobacillus ( Tang et al, 2018 ; Furukawa et al, 2020 ), and diminished Ruminococcus /Ruminococcaceae ( Lv et al, 2016 ; Furukawa et al, 2020 ) and Faecalibacterium ( Tang et al, 2018 ; Furukawa et al, 2020 ), while primary sclerosing cholangitis is linked to enlarged proportions of Veillonella ( Bajer et al, 2017 ; Kummen et al, 2017 ; Rühlemann et al, 2019 ; Cortez et al, 2020 ; Lapidot et al, 2021 ), Streptococcus ( Sabino et al, 2016 ; Bajer et al, 2017 ; Rühlemann et al, 2019 ; Lapidot et al, 2021 ), and Enterococcus ( Sabino et al, 2016 ; Bajer et al, 2017 ), as well as depressed proportions of Coprococcus ( Bajer et al, 2017 ; Kummen et al, 2017 ; Rühlemann et al, 2019 ; Kummen et al, 2021 ), Faecalibacterium prausnitzii ( Bajer et al, 2017 ; Lapidot et al, 2021 ), and Lachnospiraceae ( Bajer et al, 2017 ; Kummen et al, 2017 ; Kummen et al, 2021 ; Lapidot et al, 2021 ). Enriched gut microbiota in Wilson’s Disease are Bacteroides ( Geng et al, 2018 ; Cai et al, 2020 ) and Megamonas ( Geng et al, 2018 ; Cai et al, 2020 ), whereas Ruminococcus ( Cai et al, 2020 ) and Roseburia ( Geng et al, 2018 ) are reduced. Glycogen storage disease shows overrepresented intestinal Escherichia ( Colonetti et al, 2019 ; Ceccarani et al, 2020 ) and Proteobacteria ( Colonetti et al, 2019 ; C...…”
Section: Gut Microbiome Changes In Diseases Affecting the Human Diges...mentioning
confidence: 99%
“…Primary biliary cholangitis is associated with an elevated abundance of Streptococcus ( Lv et al, 2016 ; Tang et al, 2018 ; Furukawa et al, 2020 ), Veillonella ( Lv et al, 2016 ; Abe et al, 2018 ; Tang et al, 2018 ), Klebsiella ( Lv et al, 2016 ; Tang et al, 2018 ), Haemophilus ( Lv et al, 2016 ; Tang et al, 2018 ), and Lactobacillus ( Tang et al, 2018 ; Furukawa et al, 2020 ), and diminished Ruminococcus /Ruminococcaceae ( Lv et al, 2016 ; Furukawa et al, 2020 ) and Faecalibacterium ( Tang et al, 2018 ; Furukawa et al, 2020 ), while primary sclerosing cholangitis is linked to enlarged proportions of Veillonella ( Bajer et al, 2017 ; Kummen et al, 2017 ; Rühlemann et al, 2019 ; Cortez et al, 2020 ; Lapidot et al, 2021 ), Streptococcus ( Sabino et al, 2016 ; Bajer et al, 2017 ; Rühlemann et al, 2019 ; Lapidot et al, 2021 ), and Enterococcus ( Sabino et al, 2016 ; Bajer et al, 2017 ), as well as depressed proportions of Coprococcus ( Bajer et al, 2017 ; Kummen et al, 2017 ; Rühlemann et al, 2019 ; Kummen et al, 2021 ), Faecalibacterium prausnitzii ( Bajer et al, 2017 ; Lapidot et al, 2021 ), and Lachnospiraceae ( Bajer et al, 2017 ; Kummen et al, 2017 ; Kummen et al, 2021 ; Lapidot et al, 2021 ). Enriched gut microbiota in Wilson’s Disease are Bacteroides ( Geng et al, 2018 ; Cai et al, 2020 ) and Megamonas ( Geng et al, 2018 ; Cai et al, 2020 ), whereas Ruminococcus ( Cai et al, 2020 ) and Roseburia ( Geng et al, 2018 ) are reduced. Glycogen storage disease shows overrepresented intestinal Escherichia ( Colonetti et al, 2019 ; Ceccarani et al, 2020 ) and Proteobacteria ( Colonetti et al, 2019 ; C...…”
Section: Gut Microbiome Changes In Diseases Affecting the Human Diges...mentioning
confidence: 99%
“…Proteomic analyses comparing asymptomatic WD and control individuals showed that complement component C3 and B, and α2-macroglobulin belonging to the innate immune system and implicated in oxidative stress and inflammation are good biomarkers for early WD stages [ 150 ]. Recently, gut dysbiosis in WD patients has been settled on a diminished microbial ecosystem with loss of bacterial diversity engaged in transcription factors and ATP-dependent transporters (ABC; ATP-binding cassette) [ 151 ]. Of interest for its implication in the development of hepatic steatosis and inflammation, dysregulation of choline metabolism has been described in WD patients and in the tx-j mice model [ 152 ].…”
Section: The Need For Biomarkers For a Better Diagnosismentioning
confidence: 99%
“…Some Verrucomicrobia in the human gut might be relevant to human health, and disease prevention. Patients suffering from certain disorders like Wilson's disease have been reported to have a lower abundance of Verrucomicrobia [35] .…”
Section: Resultsmentioning
confidence: 99%